2017
DOI: 10.1101/173963
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-Wide SNPs Reveal the Drivers of Gene Flow In An Urban Population of the Asian Tiger Mosquito,Aedes albopictus

Abstract: Aedes albopictus is a highly invasive disease vector with an expanding worldwide distribution. Genetic assays using low to medium resolution markers have found little evidence of spatial genetic structure even at broad geographic scales, suggesting frequent passive movement along human transportation networks. Here we analysed genetic structure of Ae. albopictus collected from 12 sample sites in Guangzhou, China, using thousands of genome-wide single nucleotide polymorphisms (SNPs). We found evidence for passi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 87 publications
(136 reference statements)
1
20
0
Order By: Relevance
“…New methods and tools in landscape genetics can help understand past dispersal and gene flow patterns, including potential environmental parameters that limit dispersal (Schmidt, Filipović, Hoffmann, & Rašić, ; Watts et al, ). The advent of high‐density sequencing technologies has also provided increased power for landscape genomic studies conducted at spatial scales fine enough to investigate dispersal discretely over generations, and to measure individual acts of movement (Schmidt, Rašić, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…New methods and tools in landscape genetics can help understand past dispersal and gene flow patterns, including potential environmental parameters that limit dispersal (Schmidt, Filipović, Hoffmann, & Rašić, ; Watts et al, ). The advent of high‐density sequencing technologies has also provided increased power for landscape genomic studies conducted at spatial scales fine enough to investigate dispersal discretely over generations, and to measure individual acts of movement (Schmidt, Rašić, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…albopictus populations compared with Ae. aegypti (Goubert, Minard, Vieira, & Boulesteix, ), even when investigated with high‐density markers (Schmidt et al, ). However, genome‐level population genetic studies on Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the migration analysis results displayed four major migration trends with high gene ow (Nm>0.4) among the different climatic regions, corresponding with China's main trade and tourism routes. All these results revealed that human-aided dispersion might be the main reason for the similarity of populations across the different regions [22,[67][68][69][70][71][72][73][74][75][76][77][78]. This hypothesis was also veri ed via IBD analysis, which indicated that long distances were not signi cantly associated with individual genetic variation.…”
Section: Discussionmentioning
confidence: 95%